2007
DOI: 10.1021/jp067878i
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Side Chain Mediated Electroluminescence from Carbazole-Modified Polyfluorene

Abstract: In molecular design of electroluminescent (EL) conjugated polymers, introducing a charge transport moiety on a side chain is found to be a promising method for balancing electron and hole fluxes in EL devices without changing the emitting color if there is no interaction between moiety and main chain. In the case of grafting a carbazole (Cz) moiety (hole transporting) on blue emitting polyfluorene, a green emission appears with intensity comparable to the blue emission, which was attributed to a possible inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…20). 14,20,64 In our recent report, 21 we found an electroplex emission from poly(9,9-bis(N-carbazolyl-decyl)-fluorene) (Cz100PF) (Fig. 21), in which cross recombination of hole in the stacked carbazole/carbazole (Cz/Cz) dimer and electron in the nearby main chain segment under the applied electric field leads to a formation of this emitting species.…”
Section: Electroplex and Electromer: Structure And Optoelectronic Promentioning
confidence: 89%
See 1 more Smart Citation
“…20). 14,20,64 In our recent report, 21 we found an electroplex emission from poly(9,9-bis(N-carbazolyl-decyl)-fluorene) (Cz100PF) (Fig. 21), in which cross recombination of hole in the stacked carbazole/carbazole (Cz/Cz) dimer and electron in the nearby main chain segment under the applied electric field leads to a formation of this emitting species.…”
Section: Electroplex and Electromer: Structure And Optoelectronic Promentioning
confidence: 89%
“…[3][4][5][6][7][8][9][10][11][12][13] However, the dimers formed under electrical excitation, electromer and electroplex, though have been observed in organic small-molecule materials, [14][15][16][17][18] but they are often observed in conjugated polymers. [19][20][21] On the other hand, aggregate, an emitting species with a ground-state p-p interaction, does not mention often in organic small-molecule materials though it also exists, but is very important in conjugated polymer due to its long chain characteristics. 1,[22][23][24][25][26][27][28][29][30][31] Since aggregate is a ground-state emitting species, energy transfer from non-interacting isolated chain segments to aggregates can occur and thus play an important role in PL and EL properties in conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, they are referred to as electromers or electroplexes. Although there are numerous reports concerning the observation of electroplexes,14–22 surprisingly little is known about their formation pathway.…”
Section: Introductionmentioning
confidence: 99%
“…When considering the literature, it is noticeable that electroplexes and exciplexes are reported in particular for materials that contain a nitrogen atom in certain moieties. For example, electroplexes are known for combinations of organic semiconductors that contain carbazole‐moieties, amine‐moieties, oxadiazole‐moieties, and other diazole‐moieties 14–22. The same type of materials are also prone to exciplex formation.…”
Section: Introductionmentioning
confidence: 99%
“…The device emits sky blue light with two characteristic peaks at 420 and 460 nm, as for PFO, and an additional strong broad peak at 525 nm [27]. After further investigation [28], we found that the Cz groups in 15 play multiple roles as: . This efficiency is higher than that of non-end-capped polymer 3 (that is, bromine exists at each chain end) by one order of magnitude and was attributed to an efficient hole trapping at the end-capper groups [due to the lower HOMO level of triarylamine (TAA) endcapper (5.48 eV) than 3 (5.88 eV)], resulting in more chances for holes and electrons to recombine on the main chain than at sites with less efficient emissions, such as aggregates and excimer-forming sites.…”
Section: Incorporation Of Hole-transport Moiety (Htm)mentioning
confidence: 84%